Development of the JUDA program to assist at-risk children and youth: Surat Saruang - Saruang, Surat (Journal of Law and Political Affairs, 2023)
The purpose of this research was to develop the efficiency of the program module in helping children and youth. Self-assessment of children and youth and promoting the participation of government agencies, the private sector, and the public sector in giving advice and helping children and youth, people from government, private and public sectors. The results showed that there were 3 modules that had been developed: 1) Module-Child is a module for children and youth participating in the activities to register as members of the JUDA program system, 2) Module-Help is a module that looks like a chat bot area for students whose members are members who have passed self-evaluation and choose a hero to give advice, 3) Module-Hero is a module that allows kind adults in society to register as members of the JUDA program. The self-assessment of children and young people found that most children and young people had a low level of victimization. Slightly violent behavior and had a mild substance abuse behavior as well for children and youth, risk groups that should be monitored include the use of volatile substances and a small amount of marijuana. Most of them are not directly related to drugs, but there is a part in knowing and knowing that different types of drugs have been sold or is anyone using it?. The drugs that children and young people are known to use in the community are methamphetamine, ice, ecstasy, marijuana, volatile substances, and sex drugs, etc.